2014
DOI: 10.1007/s10439-014-1076-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Acute Effects of Primary Hypertension and Hypotension on the Hemodynamics of Intracranial Aneurysms

Abstract: Hemodynamics is a risk factor in intracranial aneurysms (IA). Hypertension and pharmacologically induced hypotension are common in IA patients. This study investigates how hypertension and hypotension may influence aneurysmal hemodynamics. Images of 23 IAs at typical locations were used to build patient-specific Computational Fluid Dynamics models. The effects of hypotension and hypertension were simulated through boundary conditions by modulating the normotensive flow and pressure waveforms, in turn produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…17,18 In hypertension, the RAAS has wide-ranging effects on blood pressure regulation through sodium retention, pressure natriuresis, salt sensitivity, vasoconstriction, endothelial dysfunction, and vascular injury. 8,19,20 Given these facts, in addition to the directly increasing hemodynamic stresses, 21,22 activation of the RAAS by systemic hypertension can cause vascular inflammation, injury, and remodeling and thereby contribute to the process of intracranial aneurysm rupture. 9,13 Our study found that RAAS inhibitors decreased the rupture risk of intracranial aneurysms independent of blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In hypertension, the RAAS has wide-ranging effects on blood pressure regulation through sodium retention, pressure natriuresis, salt sensitivity, vasoconstriction, endothelial dysfunction, and vascular injury. 8,19,20 Given these facts, in addition to the directly increasing hemodynamic stresses, 21,22 activation of the RAAS by systemic hypertension can cause vascular inflammation, injury, and remodeling and thereby contribute to the process of intracranial aneurysm rupture. 9,13 Our study found that RAAS inhibitors decreased the rupture risk of intracranial aneurysms independent of blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…Our flow conditions were derived from normal subjects and scaled with the patient-specific inflow vessel sizes, but the effects of co-morbidities such as hypertension were not considered. While our assumptions may be reasonable [23], the effects of other co-morbidities should be investigated in future studies. In addition, we considered uniaxial loading, recognizing that in vivo loading is closer to equi-biaxial.…”
Section: Discussionmentioning
confidence: 99%
“…There now exist substantial databases of clinical and imaging data from patients with both ruptured and unruptured aneurysms, for example through the @neurIST project (with nearly 500 patients); for full details of the processing toolchain, see Bogunovic et al (2011) andVilla-Uriol et al (2011). These provide populations from which virtual populations can be reconstructed and studies performed to quantify the effects of parameters such as hypertension and hypotension, Sarrami-Foroushani et al (2015).…”
Section: Cerebral Aneurysmsmentioning
confidence: 99%